International criminal justice critical perspectives and new challenges - Andreopoulos, George; Barberet, Rosemary; Levine, James P.; SpringerLink (Online service). (New York London Springer, 2011)
In recent years, justice-related issues have figured prominently on the international agenda. This expansion of the justice space is a product of a growing demand for accountability in world politics. Whether the issue is addressing heinous crimes such as genocide, war crimes and crimes against humanity in situations of armed conflict, confronting the inability or reluctance of governments to protect their own populations, or responding to the challenges posed by transnational terrorism, the international community has witnessed the proliferation of institutions and mechanisms, as well as the dynamic interplay between domestic and international processes, in the pursuit of justice-sensitive outcomes. International and hybrid tribunals, UN-led and domestic counter-terrorist initiatives, and the use of force for human protection purposes have demarcated the space within which ethical, political, and legal debates have unfolded in the quest for a more humane world order. In International Criminal Justice: Legal and Theoretical Perspectives, the authors address some of the most important debates surrounding key mechanisms and processes involved in this quest, and assess the merits of contending approaches to the promotion of international justice norms. This volume will contribute to the ongoing debate on the challenges, as well as opportunities, facing the justice agenda in its effort to shape developments in an increasingly interdependent world
International Criminal Justice Foreword Introduction Contents Contributors It Counts, But Only When It Does Not Matter? Evolving Standards of Decency and the Law of Other Countries Robert F. Schopp Just War Claims: Historical Theory, Abu Ghraib, and Transgressive Rhetoric Toy-Fung Tung Policing the Human: Lawfare and Humanitarianism J. Paul Narkunas The Big Chill: First Amendment Protections and the War on Terror Martin Wallenstein Terrorism: The Dilemma of Response Elena Pokalova Divided We Stand? American and European Perspectives in the Fight Against Transnational Terrorism M. Victoria Pérez-Ríos United Nations Counterterrorist Strategies and Human Rights George Andreopoulos Can Domestically Seated War Crimes Tribunals Generate Positive Externalities? A Case Study of the Special Court for Sierra Leone Christopher E.S. Warburton and Richard F. Culp
Includes bibliographical references and index
Electronic reproduction
Keywords: International criminal law -- Congresses; Criminal procedure (International law) -- Congresses; Criminal justice, Administration of -- Congresses; International crimes -- Congresses; International cooperation -- Congresses